Antioxidant potential of herbs and spices during deep frying of ghee. (18th April 2014) - Patel, Shriyesh; Shende, Sneha; Arora, Sumit; Singh, Ram Ran Bijoy; Rastogi, Subha; Singh Rawat, Ajay Kumar
<x xml:space="preserve">Abstract</x> The present study was carried out to evaluate antioxidant potential of ashwagandha, clove, coriander, green tea, shatavari and vidarikand extracts as compared to BHA. Clove, coriander and green tea extracts showed significantly higher antioxidant activity than vidarikand, shatavari and ashwagandha extracts. Radical‐scavenging activity by DPPH model system revealed that clove and green tea extracts were superior to other extracts. All the natural antioxidants significantly reduced the formation of peroxides, FFA, thiobarbituric acid value and conjugated dienes. Ghee with added clove, green tea and coriander extracts showed higher induction period as compared to ghee containing vidarikand, ashwagandha, shatavari or BHA.